Penggunaan Majas Perbandingan dalam Novel Luka Cita Karya Valerie Patkar - Ulfatun Khasanah; Muslim (Lingua Franca, 2025)
This study examines the utilization of comparative figurative language in Luka Cita, a novel by Valerie Patkar, through a stylistic analytical framework. The research centers on three dominant types of figurative expression—metaphor, personification, and simile—investigated for their contribution to semantic enrichment, emotional resonance, and literary aesthetics. Employing a qualitative descriptive method, the data were acquired through meticulous textual analysis and classification, grounded in Masruchin’s (2017) taxonomy of comparative tropes. The analysis identifies 24 occurrences of metaphor, 14 of personification, and 12 of simile throughout the novel. These stylistic elements perform significant narrative functions: metaphors provide a concrete representation of abstract feelings; personification attributes human characteristics to inanimate objects, thereby intensifying the psychological depiction of characters; and similes create direct analogies that amplify narrative imagery. Such figurative constructions are not employed solely for decorative purposes but as integral tools for constructing meaning and enhancing the reader’s interpretative engagement. This investigation contributes to literary stylistics, particularly in modern Indonesian prose. It demonstrates how Valerie Patkar strategically employs language to articulate intricate emotional states, internal conflicts, and thematic depth. Furthermore, the effective deployment of comparative figures of speech strengthens the emotional rapport between the narrative and its audience. Hence, the findings affirm that figurative language is pivotal in deepening literary interpretation and unveiling stylistic intent.